Resolución de problemas de la estructura aditiva de los números enteros con estudiantes de grado séptimo a partir de las seis grandes categorías de relaciones aditivas de vergnaud (2016)
Throughout history, integers have been difficult to accept and currently difficult to understand (Gonzales, Iriarte et al., 1999) by basic education students, since the operations and properties of numbers are ingrained. natural at the concrete level, which means that when the signed numbers appear, it generates a conflict for them to assimilate this new knowledge since it is difficult to find them on the level of reality.